2021
DOI: 10.3329/bjid.v7i2.51507
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profiles and Sources of Infection among Septic Patients admitted at ICU of a Public Hospital in Dhaka City

Abstract: Background: Sepsis occurs due to different sources of infection. Objective: The purpose of the present study was to see the demographic profiles and sources of infection among septic patients admitted at ICU of a public hospital in Dhaka City. Methodology: This descriptive cross sectional study was conducted in the Intensive Care Unit of the department of Anaesthesia Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, Bangladesh over a period of 12 months start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Pneumonia was diagnosed as the most frequent respiratory tract infection in children (37%) as well as in adults (27%) [5]. Another study, including 69 patients with severe sepsis and septic shock, reported that the common origins of infection were abdomen (43.5%), central nervous system (CNS) (21.7%), urogenital tract (17.4%), respiratory tract (14.5%) and gastrointestinal tract (2.9%) [27]. The high mortality rate due to sepsis in developing countries might be due to the poorly understood epidemiology of sepsis, high prevalence of immunocompromised patients (HIV/AIDS) and lack of adequate facilities for treatment.…”
Section: Epidemiological Data Associated With Sepsis Patients In Sout...mentioning
confidence: 99%
“…Pneumonia was diagnosed as the most frequent respiratory tract infection in children (37%) as well as in adults (27%) [5]. Another study, including 69 patients with severe sepsis and septic shock, reported that the common origins of infection were abdomen (43.5%), central nervous system (CNS) (21.7%), urogenital tract (17.4%), respiratory tract (14.5%) and gastrointestinal tract (2.9%) [27]. The high mortality rate due to sepsis in developing countries might be due to the poorly understood epidemiology of sepsis, high prevalence of immunocompromised patients (HIV/AIDS) and lack of adequate facilities for treatment.…”
Section: Epidemiological Data Associated With Sepsis Patients In Sout...mentioning
confidence: 99%